Forum Kampung Bahasa (FKB) dalam Meningkatkan Potensi Learning Society Kampung Inggris Pare Tahun 2011-2022 - Eva Nurlaeli; Septina Alrianingrum (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study was motivated by the surge of newcomers and language schools in Kampung Inggris Pare during 2009–2010, which triggered social problems such as unhealthy competition among language schools and conflicts among newcomers leading to the establishment of the Language Village Forum (FKB) in 2011. The research questions for this study are: (1) What was the background behind the establishment of the FKB? (2) What role does the FKB play in managing language institutions? and (3) How has the FKB contributed to enhancing the potential of a learning society from 2011 to 2022? The methodology employed is the historical method, encompassing heuristics, source criticism, interpretation, and historiography, utilizing primary sources such as interviews, government regulations, and archives, as well as secondary sources. The research findings indicate that the FKB plays a crucial role in managing institutions in Kampung Inggris. Although coordination was less than optimal from 2011 to 2018, the 2018 trademark conflict served as a turning point in the organization’s awareness. From 2019 to 2022, the FKB successfully improved institutional management, established strategic partnerships, and helped Tulungrejo Village achieve a MURI (Indonesian World Records Museum) record. The FKB also succeeded in enhancing the potential of the learning society through community empowerment, synergy with the local government, and efforts to build a conducive learning environment.